MAHASISWA PLP MENERAPKAN MIND MAPPING UNTUK MENINGATKAN HASIL BELAJAR PAI PADA SISWA KELAS X DI SMK JAYABEKA 01 KARAWANG - Nurhalimah; Kurnia Piqi; Kaka Habibi; Mitra Sasmita; Herdian Kertayasa (STKIP Subang, 2026)
The purpose of this study is to examine how Mind Mapping is used in planning Islamic Religious Education (PAI) lessons at SMK Jayabeka 01 Karawang and how it impacts students' academic achievement. Data were collected through classroom observation, in-depth interviews, and document analysis using a qualitative approach. The results of the study indicate that the mind mapping method is effective in helping students understand PAI concepts and enhancing their creativity and engagement in the learning process. This method is incorporated into the Semester Learning Plan (RPS) designed by the teacher, and students receive initial training to help them create Mind Maps. These findings encourage the application of the mind mapping method in PAI learning, in line with the principles of a flexible curriculum that supports student creativity. The results show that this method increases students' motivation and self-confidence, despite obstacles such as limited time and students having difficulty creating a Mind Map.